The Effectiveness Probiotic Drink of Salak Bali (Salacca zalacca) in Inhibiting Growth of Escherichia coli - Nadya Treesna Wulansari; A.A. Istri Mas Padmiswari; Ida Ayu Manik Damayanti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Salak bali (Salacca zalacca) is one of the local fruit varieties cultivated in Bali. This fruit contains antioxidants, so that it is potential to be used as a probiotic drink. Probiotic drinks containing live microbes can inhibit the growth of pathogenic microbes and balance the microbes in the intestines so that they can affect the health of those who consume them. This study aimed to determine the effectiveness of the probiotic drink of salak bali fruit juice (Salacca zalacca) in inhibiting the growth of Escherichia coli. The study employed experimental with a completely randomized design. Salak juice was fermented for 18 days and harvested every 3 days, then an antibacterial test was carried out. The data were analyzed by using analysis of variance (ANOVA) followed by Duncan's Multiple Range Test (DMRT) at a 5% significance level. The finding showed that probiotic drink of salak bali fruit juice effective to inhibiting the growth of Escherichia coli. Optimal antibacterial growth was seen on the 15th day of fermentation with an inhibition zone of 8.13 ± 0.40 mm. The presence of inhibition caused by the phytochemical content found in salak fruit, SCOBY contained in drinks, and the length of the fermentation process.